Preconcentration, speciation, and determination of key elements in biological samples in Latin America - Pacheco, Pablo Hugo; Gil, Raul Andres; Martinez, Luis Dante; Smichowski, Patricia Nora (Springer Heidelberg, 2013)
Fil: Pacheco, Pablo Hugo. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico San Luis. Instituto de Química de San Luis; Argentina